2010
DOI: 10.1246/cl.2010.958
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Relaxation in the Supercooled Liquid State of Ethylbenzene: Thermal Studies Using a Prototype DTA Sensor for the Study of Vapor-deposited Samples

Abstract: A prototype sensor for differential thermal analysis (DTA) was developed for in situ studies of the thermal behavior of molecular films vapor-deposited onto a cold substrate in a vacuum. The system was applied to the study of ethylbenzene (EB). By raising the temperature at a constant rate, we observed in the supercooled liquid (SCL) state a small exothermic peak simultaneously with the characteristic light scattering reported previously. These observations and additional optical experiments on the irreversibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 11 publications
(18 reference statements)
5
22
0
Order By: Relevance
“…The present experiments would have detected an intermediate state with a mobility three times that of the conventional liquid, a case that had been discussed previously. 24 We also anticipate that if IMC behaved analogous to what has been reported for iso-propylbenzene or ethylbenzene, 45,46 our experiments would have provided an indication for a metastable liquid that differs from the conventional supercooled liquid.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The present experiments would have detected an intermediate state with a mobility three times that of the conventional liquid, a case that had been discussed previously. 24 We also anticipate that if IMC behaved analogous to what has been reported for iso-propylbenzene or ethylbenzene, 45,46 our experiments would have provided an indication for a metastable liquid that differs from the conventional supercooled liquid.…”
Section: Discussionsupporting
confidence: 71%
“…These optical features were observed immediately following the annealing from the ultrastable glassy state, disappeared after annealing, and remained absent for supercooled liquids formed by cooling the melt. 45,46 Capponi et al reported an analogous feature observed by dielectric spectroscopy. 47 On the other hand, a recent SIMS study 26 suggested that the self-diffusion coefficient D of the liquid transformed from ultrastable IMC glass does not differ from the value of D of the conventional supercooled counterpart.…”
Section: Resultsmentioning
confidence: 62%
“…High density glass is obtained by vapor deposition of ethylbenzene on cold substrates, in addition to thermodynamically unstable low density glass [42]. When the temperature is raised in this system, a structural relaxation occurs to the unstable low density glass, while high density glass transforms directly to supercooled liquid [43]. States of WCA spheres also melted when kept at temperature T = 140 for state E, at T = 135 for states A and B, at T = 134 for state C and D, and at T = 131 for state F. State B kept at T = 135 remained to be so for a certain time, i.e., for t = 1087 (i.e., In Figure 12, we show the self van Hove correlation function F (r xyz , t) in the hopping states A, B, C, D, and E of WCA spheres.…”
Section: Three-dimensional Hopping In Monodispersed Glassmentioning
confidence: 99%
“…Immediately after this change, the relaxation from LDL to another SCL took place as indicated by the significant depression of the reflected light intensity. 11,22 Note that this depression is not due to the change in the interference condition but is due to light scattering mainly in the bulk of the sample. 11 In addition, it should be emphasized that no indication of crystallization could be detected in this temperature region from Raman spectra and X-ray diffraction patterns.…”
Section: Interpretation Of Observed Evolution Of Reflectedmentioning
confidence: 99%
“…11,22 Note that this depression is not due to the change in the interference condition but is due to light scattering mainly in the bulk of the sample. 11 In addition, it should be emphasized that no indication of crystallization could be detected in this temperature region from Raman spectra and X-ray diffraction patterns. 24 When relaxation to the new SCL was almost completed, the transparency of the sample was recovered to half the level of the maximum intensity.…”
Section: Interpretation Of Observed Evolution Of Reflectedmentioning
confidence: 99%